2021
DOI: 10.3390/su13095140
|View full text |Cite
|
Sign up to set email alerts
|

Aeroponics Root Chamber Temperature Conditioning Design for Smart Mini-Tuber Potato Seed Cultivation

Abstract: The aeroponic plant root environment has a significant role in producing high-quality seed tuber potatoes. However, in lowland and tropical regions, the aeroponic system cannot yield high-quality potato seed because the average environment temperature year-round is high. In a high-temperature environment, the potato plant roots cannot optimally absorb the nutrient solution for healthy plant growth. This paper presents the method used to maintain the aeroponics root chamber temperature conditions. An air condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The aeroponic farming system allows control of the root temperature, independent of the location and elevation of the area. This can be achieved by modifying the air of the root chamber through the use of actuators such as fan [6] and external refrigeration [12]. It is reported that the temperature for the root chamber should not exceed 30 °C [1].…”
Section: Research Methods 21 Key Aeroponic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The aeroponic farming system allows control of the root temperature, independent of the location and elevation of the area. This can be achieved by modifying the air of the root chamber through the use of actuators such as fan [6] and external refrigeration [12]. It is reported that the temperature for the root chamber should not exceed 30 °C [1].…”
Section: Research Methods 21 Key Aeroponic Parametersmentioning
confidence: 99%
“…For an aeroponic system, a successful local monitoring for temperature, humidity, and pH in potato production was reported [11]. Kuncoro et al [12] reported an increase in potato production by implementing local monitoring and conditioning of the root chamber temperature. Some others reported on the online monitoring of aeroponic system [13]- [16].…”
mentioning
confidence: 99%
“…151 A normal light intensity gets radiated or reflected in protected cultivation, vertical farming, and closed systems for soilless farming, but a high intensity of light reflects in open systems, soil affected regions, and stress areas in soilless farming. 152 Light intensity is the basis of and essential for photosynthesis, respiration, flowering stimulus, phytochrome enzymatic metabolism, plant growth hormone regulation, stress regulation, and gene regulation in crops for creating assimilatory products. 153 Agricultural and horticultural crops require distinct light duration (hours) per day for regulation of growth and physiological processes in open systems, closed systems, protected cultivation, vertical farming, soil affected areas, stress areas, and prone areas.…”
Section: Crop Productionmentioning
confidence: 99%
“…Light is the most imperative factor for water based culture and substrate based culture . A normal light intensity gets radiated or reflected in protected cultivation, vertical farming, and closed systems for soilless farming, but a high intensity of light reflects in open systems, soil affected regions, and stress areas in soilless farming . Light intensity is the basis of and essential for photosynthesis, respiration, flowering stimulus, phytochrome enzymatic metabolism, plant growth hormone regulation, stress regulation, and gene regulation in crops for creating assimilatory products .…”
Section: Factors Influencing Soilless Culture and Crop Productionmentioning
confidence: 99%
“…In aeroponics systems, the root development process is crucial for the plant’s growth performance. In order to optimize the plant’s aerial parts in aeroponic culture, the appropriate value definition of irrigation water pressure, droplet size and fogging interval is needed to improve the continuous water and nutrient availability [ 30 , 31 ]. Recently, non-invasive monitoring systems have been proposed for the study of vegetative growth parameters in roots and leaves developed in greenhouses [ 31 ].…”
Section: Introductionmentioning
confidence: 99%